Percutaneous Nephrolithotomy in Paediatric Population: A Single Center Experience - Adhikari, Mahesh Bahadur; Karna, Sumeet; Adhikari, Kinju; Baidya, Jagdish Lal (Journal of Nepal Health Research Council, 2020)
Background: Management of paediatric stone disease is challenging as they are considered high risk group. Percutaneous nephrolithotomy is minimally invasive procedure with definite advantages in terms of higher stone clearance in single session and no long term effect in renal function.Methods: Retrospective study was done including all patients upto the age of 18 years who underwent Percutaneous nephrolithotomy from January 2010 to December 2018 in our center after taking approval from ethical committee. Data was collected regarding gender, operative side, operative time duration, hospital stay, post-operative decrease in hemoglobin, stone size, Guy’s stone score and early post-operative complications with Clavien-Dindo grade.Results: Percutaneous nephrolithotomy was done in 48 renal units in 44 patients. 28 patients were boys and 16 were girls with mean age of 10.91 ± 5.22 years and mean stone size 17.16 ± 6.43 mm. 91.6% of cases had Guy’s stone score of 1 and 2. Standard percutaneous nephrolithotomy was done in 21 renal units, mini percutaneous nephrolithotomy in 24 renal units and supermini percutaneous nephrolithotomy was done in three renal units with total stone free rate of 93.4%. Three patients required extracorporeal shockwave lithotripsy for significant residual stone. Average post-operative hemoglobin drop was 1.2 gm%. Overall complications rate was 18.1% with 4.5% of complications being grade 1 and 2 whereas 13.6% were Grade 3.Conclusions: Percutaneous nephrolithotomy is safe and feasible in paediatric patients with large stone burden, complex anatomy or shock-wave lithotripsy failure with acceptable complication and stone free rate. Keywords: Endourology; paediatric; percutaneous nephrolithotomy; PNL; urolithiasis